2022
DOI: 10.3389/fsurg.2022.929103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of jumbo cup in revision total hip arthroplasty: A systematic review

Abstract: IntroductionMany studies have reported the clinical outcomes of a jumbo cup in revision total hip arthroplasty (rTHA) with acetabular bone defect. We conducted a systematic review to access the survivorship and clinical and radiological outcomes of a jumbo cup in rTHA.MethodsA systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A comprehensive literature search from PubMed, MEDLINE, EMBASE, and the Cochrane Database of Systematic Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The survival rate of TT cups was in line with the survival rate of uncemented Jumbo cups. In a recent systematic literature review, Wang et al ( 15 ) reported an overall reoperation rate of 8.6% with a cup survivorship of 95%. The higher survivorship reported with the Jumbo cup could be explained due to the less severe acetabular bone deficiency of patients included in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate of TT cups was in line with the survival rate of uncemented Jumbo cups. In a recent systematic literature review, Wang et al ( 15 ) reported an overall reoperation rate of 8.6% with a cup survivorship of 95%. The higher survivorship reported with the Jumbo cup could be explained due to the less severe acetabular bone deficiency of patients included in their study.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a retrospective review of consecutive patients who underwent revision THA using MA combined with ARR in our institution between January 2014 and March 2015. We chose the cup–cage system when the size of the acetabular defects were extensive for the jumbo cup (males over 64-mm, females over 60-mm) [ 36 ] to cover. We assessed the acetabular defect using preoperative 3D-CT in all revision THA cases, and we prepared ARR with MA for the cases that showed the acetabular defect with more than a 2 cm acetabular component migration, which means Paproski classification Type III or IV.…”
Section: Methodsmentioning
confidence: 99%